KONSISTENSI HUKUM WORLD TRADE ORGANIZATION (WTO) MENGENAI PRINSIP MOST FAVORED NATION (MFN) ATAS REGIONALISME DAN PANDANGANNYA TERHADAP ASEAN ECONOMIC COMMUNITY (AEC) - Sutanto, Marko Cahya (Veritas et Justitia, 2015)
In 2015, Indonesia and other ASEAN members have a commitment to establish a single market region, i.e. free flow of goods and service, termed ASEAN Economic Community (hereinafter âAECâ). This arrangement is contrary to Most Favored Nation (MFN) principle under the General Agreement on Tariffs and Trade 1994, (hereinafter âGATTâ). This paper aims to address the said violation according to the WTO/GATT law by analyzing (1) the general obligations and exceptions under the WTO/GATT, (2) regionalism in general and its existence in Southeast Asia, and (3) the interpretation of WTOâs compromise to regionalism. Under the GATT, there is a general obligation for members to treat their trading partners equally and give the same benefits to other members. However, there is an exception to this principle under article XXIV of the GATT, which based on the notion that regional trade agreements are a building block for multilateral openness. Yet, before applying this exception to the case at hand, AECâs form must be determined. AECâ has a structure of Free-Trade Area (hereinafter âFTAâ) with a single market adhere to it, which according to WTOâs database there is one in force at the moment, namely ASEAN Free Trade Area (hereinafter âAFTAâ). AFTA is not the equivalent to AEC because it covers more than just goods. Thus, the answer to apply the exception to AEC is inconclusive because even though it fits normatively, it does not have the necessary legitimacy.